2014
DOI: 10.1111/jtsb.12074
|View full text |Cite
|
Sign up to set email alerts
|

Kurt Lewin's Leadership Studies and His Legacy to Social Psychology: Is There Nothing as Practical as a Good Theory?

Abstract: This paper re‐examines Kurt Lewin's classic leadership studies, using them as a concrete example to explore his wider legacy to social psychology. Lewin distinguished between advanced “Galileian” science, which was based on analysing particular examples, and backward “Aristotelian” science, which used statistical analyses. Close examination of the way Lewin wrote about the leadership studies reveals that he used the sort of binary, value‐laden concepts that he criticised as “Aristotelian”. Such concepts, espec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
35
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 55 publications
0
35
0
3
Order By: Relevance
“…Some are concerned that the scope accorded to the leader by Lewin can result in the abuse of democratic participation as a means of engineering the outcomes desired by those in power (Graebner, 1986(Graebner, , 1987Billig, 2015). One difficulty is that Lewin does not offer any idea as to how to differentiate strong democratic leadership from the "excessive strength" that "might tip the balance towards improper pseudo-democratic, manipulative, or authoritarian methods" (Graebner, 1987: 143).…”
Section: A Unitarist Versus Plural View Of Organization?mentioning
confidence: 99%
See 1 more Smart Citation
“…Some are concerned that the scope accorded to the leader by Lewin can result in the abuse of democratic participation as a means of engineering the outcomes desired by those in power (Graebner, 1986(Graebner, , 1987Billig, 2015). One difficulty is that Lewin does not offer any idea as to how to differentiate strong democratic leadership from the "excessive strength" that "might tip the balance towards improper pseudo-democratic, manipulative, or authoritarian methods" (Graebner, 1987: 143).…”
Section: A Unitarist Versus Plural View Of Organization?mentioning
confidence: 99%
“…It is argued in the absence of proper representation, that democratic methods can operate as a control technique for management. Billig (2015) summons attention to how apparently neutral phraseology of the kind used by Lewin and his associates, such as "would you like to?...) conveys a "preference structure" for agreement, such that agreement is invited and disagreement can be problematic (Pomerantz, 1984).…”
Section: A Unitarist Versus Plural View Of Organization?mentioning
confidence: 99%
“…However, it was observed that children behaved in a way that they tended not to consume much energy when autocratic and laisses fair leadership behaviours were shown to group members. In the long term, democratic leadership style was found to be most contributing to the production (Billig, 2015).…”
Section: Blake-moutonmentioning
confidence: 97%
“…In laisses fair leadership, employees are never interfered and never intervened (Harrison, 2018). Kurt Lewin and his team observed in their research conducted on mask producing children that autocratic leadership style significantly increased production in the short term (Billig, 2015). However, it was observed that children behaved in a way that they tended not to consume much energy when autocratic and laisses fair leadership behaviours were shown to group members.…”
Section: Blake-moutonmentioning
confidence: 99%
“…En el corazón de las propuestas de la investigación acción y el maoísmo, se encuentra presente la idea hegeliana de Aufhebung: la superación de tensiones llevadas hacia un nuevo nivel. En Lewin la superación es vista como un logro grupal, obtenido gracias a que fuerzas opuestas pueden ser estabilizadas a través de un determinado arreglo entre los participantes (Billig, 2015). En cambio, en Zendog la superación es concebida como el modo en que las contradicciones en el seno del pueblo son resueltas a través del empleo de la dialéctica en la política (Zendog 1975, p. 143).…”
unclassified